β-Tricalcium phosphate incorporated natural rubber latex membranes for calvarial bone defects: Physicochemical, in vitro and in vivo assessment - Giovanetti, Karina; Tuma, Rafael Brull [UNESP]; Sant'Ana Pegorin Brasil, Giovana [UNESP]; Miranda, Matheus Carlos Romeiro; Borges, Felipe Azevedo [UNESP]; Tanaka, Jean Lucas [UNESP]; Burd, Betina Sayeg [UNESP]; Cortellazzi, Karine Laura; Guerra, Nayrim Brizuela [UNESP]; Mussagy, Cassamo Ussemane; Floriano, Juliana Ferreira [UNESP]; dos Santos, Lindomar Soares; et al. (Elsevier, 2024)
Natural rubber latex membrane (NRL) is a biocompatible macromolecule that stimulates angiogenesis and promotes bone repair. Similarly, β-tricalcium phosphate (β-TCP) is an osteoconductive and osteoinductive bioceramic widely used as a bone substitute. Here, we investigated the combined use of these biomaterials in the guided bone regeneration process for calvarial defects in rats. Physicochemical characterization was performed to evaluate the interaction between β-TCP and NRL. Membrane toxicity was assessed using MC3T3 osteoblasts culture and in vivo assays with Caenorhabditis elegans. Lastly, NRL membranes, NRL incorporated with β-TCP membranes (NRL-β-TCP), and a periosteum-only (control group) were tested on rodents. MC3T3 cells adhered to membranes, preserving their morphology and intercellular connections. NRL-β-TCP membranes demonstrated no toxicity in larvae, which maintained their sinusoidal wave shape. Tests results on rodents revealed statistical difference between the groups at 60 days post-operation. NRL-β-TCP (56.1 ± 14.0 %) had an average 1.48-fold higher than the control group (38.0 ± 9.1 %), with tissue production and bone remodeling. Our qualitative histological analyses revealed that membranes significantly accelerated bone formation without any signs of inflammatory reactions. We conclude that NRL-β-TCP has potential to be used for flat bone regeneration, with osteoconductive properties, being a cheap, biocompatible, and effective occlusive barrier.
Keywords: Bioceramic; Caenorhabditis elegans; Guided bone regeneration; Natural rubber; Occlusive barrier